Repellent Activity of Waste Extract from Two Local Medicinal Plant Against Rice Weevil (Sitophilus oryzae) - Priyantini Widiyaningrum; Devy Candrawati; Dyah Rini Indriyanti; Bambang Priyono (Biosaintifika: Journal of Biology & Biology Education, 2019)
In order to find natural and inexpensive bioinsecticides, the active compound of waste extract from two medicinal plants were analyzed.  Ethanolic extracts of Amomum cardamomum and Zingiber zerumbet were evaluated under laboratory conditions for their repellency against rice weevil (Sitophilus oryzae, L.). Four extracts concentration were tested in this research, i.e: 25, 50, 75 and 100%.  Efficacy was measured based on the response of rice weevil in preference tests using Y Olfactometer Tube, then the results were converted into the Percentage Repellency (PR) and Preference Index (PI). The PR data were analyzed using ANOVA, whereas PI values were analyzed descriptively. The result showed that the PR were significantly (LSD test; α 0.05) and revealed that waste extracts repel the rice weevil at 100% solution.  The highest PR was found at 100% solution in both extracts, however, statistically the repellency of A. cardamomum waste extract was higher than Z. zerumbet’s. Likewise, the PI of both extracts showed negative value at 75 and 100% concentration. This study concluded that extract of A. cardamomum and Z. zerumbet wastes have repellent effect against rice weevil and A. cardamomum repellency is better than Z. zerumbet. The findings of this study can provide a useful information for development of a rice weevil repellent extracted from waste product of medicinal plants that is more economically and environmentally friendly than synthetic insect repellents.